2002
DOI: 10.1037/0022-006x.70.2.369
|View full text |Cite
|
Sign up to set email alerts
|

Self-definition as a survivor of childhood sexual abuse among Navy recruits.

Abstract: This study explored how specific childhood sexual experiences (CSEs) might be related to selfidentification as a victim of sexual abuse and to gender differences in self-defined victimization. Hierarchical logistic regression was used to estimate the relationship of demographic and CSE characteristics with self-definitions. The characteristics most strongly associated were threats-force, incest, and younger age at the time of the experience. Men were less likely than were women to acknowledge abuse and to repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
5
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 20 publications
9
36
5
1
Order By: Relevance
“…That is, some research finds that males are less likely to disclose compared to females (Buhrmester & Prager, 1995;DeVoe & Faller, 1999;Hershkowitz, Horowitz, & Lamb, 2005;Stander et al, 2002), whereas others find no gender differences (DiPietro et al, 1997;Goodman-Brown, Edelstein, Goodman, Jones, & Gordon, 2003;Kellogg & Hoffman, 1995;Varia et al, 1996). Although disclosure studies that focus on race and ethnicity are limited (Paine & Hansen, 2002), some researchers have found that Whites are more likely to disclose (Lon-don, Bruck, Ceci, & Shuman, 2005;Stander et al, 2002;Toukmanian & Brouwers, 1998); other researchers find no ethnic differences (Bottoms, Rudnicki, & Epstein, 2007;Kellogg & Hoffman, 1995;London, Bruck, Ceci, & Shuman, 2007). In terms of age, disclosure research is equivocal, with some studies finding that older children are more likely to disclose than younger children (Buhrmester & Prager, 1995;DiPietro et al, 1997;Goodman-Brown et al, 2003;Hershkowitz et al, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, some research finds that males are less likely to disclose compared to females (Buhrmester & Prager, 1995;DeVoe & Faller, 1999;Hershkowitz, Horowitz, & Lamb, 2005;Stander et al, 2002), whereas others find no gender differences (DiPietro et al, 1997;Goodman-Brown, Edelstein, Goodman, Jones, & Gordon, 2003;Kellogg & Hoffman, 1995;Varia et al, 1996). Although disclosure studies that focus on race and ethnicity are limited (Paine & Hansen, 2002), some researchers have found that Whites are more likely to disclose (Lon-don, Bruck, Ceci, & Shuman, 2005;Stander et al, 2002;Toukmanian & Brouwers, 1998); other researchers find no ethnic differences (Bottoms, Rudnicki, & Epstein, 2007;Kellogg & Hoffman, 1995;London, Bruck, Ceci, & Shuman, 2007). In terms of age, disclosure research is equivocal, with some studies finding that older children are more likely to disclose than younger children (Buhrmester & Prager, 1995;DiPietro et al, 1997;Goodman-Brown et al, 2003;Hershkowitz et al, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Disclosure studies generally occur in two formats. In the first version, individuals who admit experiencing maltreatment are generally asked to disclose the details of their abusive experiences and are then reinterviewed at a later date about the same incidents (Stander, Olson, & Merrill, 2002). Alternatively, the subjects of a disclosure study may also include children referred to a clinic after an alleged sexual abuse incident who are interviewed to determine if they are willing to personally disclose the abuse when asked specifically about the incident (DeVoe & Faller, 1999;DiPietro, Runyan, & Fredrickson, 1997;Kellogg & Hoffman, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, participants were asked to indicate whether they had ever been sexually assaulted, but were not given a definition of sexual assault, nor were they asked whether the assault involved sexual penetration or resulted in physical injury. We have previously reported that specific operational definitions of childhood abuse yield a combined rate for childhood physical, sexual, and verbal abuse that is twice that obtained using self-definitions (Olson, Stander, & Merrill, 2000;Stander et al, 2002). Operational definitions may be more sensitive in identifying individuals at risk for PTSD as a result of abuse.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Studies of combat veterans have also documented rates of 15% to 36% (Sutker, Bugg, & Allain, 1990). Large percentages of the general population have experienced a traumatic event that might lead to PTSD (Merrill, Hervig, & Newell, 1995;Stander, Olson, & Merrill, 2002). Resnick, Kilpatrick, Dansky, Saunders, and Best (1993) interviewed a nationally representative sample of women to find out how many had been victims of a serious crime (rape, sexual or physical assault, homicide of a friend or family member) or had experienced a life-threatening situation (natural disaster, serious accident, injury).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The coping strategies (Simon, Feiring, & McElroy, 2010) and cognitive appraisals (Lab & Moore, 2005;Stander et al, 2002) sexual abuse survivors use are critical ingredients in how men and boys understand, define, and experience victimization. Avoidant coping strategies, which are associated with worse outcomes, are more common among sexually abused boys (Simon et al, 2010).…”
Section: Intrapsychic Factorsmentioning
confidence: 99%